2020
DOI: 10.3390/microorganisms8091306
|View full text |Cite
|
Sign up to set email alerts
|

Refining the Galleria mellonella Model by Using Stress Marker Genes to Assess Clostridioides difficile Infection and Recuperation during Phage Therapy

Abstract: The Galleria mellonella is an effective model for probing Clostridioides difficile interactions with phages. Despite valuable insights from this model, the larvae are not easily amenable to assessing detailed clinical responses to either bacteria or phages. Here, larval survival, colonisation and toxin levels were compared to expression profiles of 17 G. mellonella stress genes to monitor Clostridiodes difficile infection (CDI), and recuperation during phage therapy. The larvae were infected with a ribotype 01… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 53 publications
(111 reference statements)
4
28
0
Order By: Relevance
“…Previous data from our laboratory and others have shown that the Galleria model is useful and that it correlates to large scale animal models. More broadly, the G. mellonella model is cheap and is a valuable biological tool to study the virulence and pathogenicity of pathogens including Salmonella , and pharmacokinetics of anti-infectives including phage therapy ( Thomas et al, 2013 ; Nale et al, 2016a , 2020 ). In this study, G. mellonella larvae were colonized with representative isolates and detail evidence of the efficacy of different phage therapeutic regimens to prevent and reduce colonization in the model was obtained and is presented.…”
Section: Introductionmentioning
confidence: 99%
“…Previous data from our laboratory and others have shown that the Galleria model is useful and that it correlates to large scale animal models. More broadly, the G. mellonella model is cheap and is a valuable biological tool to study the virulence and pathogenicity of pathogens including Salmonella , and pharmacokinetics of anti-infectives including phage therapy ( Thomas et al, 2013 ; Nale et al, 2016a , 2020 ). In this study, G. mellonella larvae were colonized with representative isolates and detail evidence of the efficacy of different phage therapeutic regimens to prevent and reduce colonization in the model was obtained and is presented.…”
Section: Introductionmentioning
confidence: 99%
“…They also require less expertise to work with, and their cells are similar enough to human cells to allow comparable impact assessment and inference [ 44 ]. Phages have been shown to be stable in these models and the route of phage administration depends on the pathogen under investigation [ 44 , 59 , 67 ]. Through colonisation, survival and immune response studies, these models have been instrumental in determining phage therapeutic potential [ 44 , 59 , 67 ].…”
Section: Efficacy Testing In Complex In Vitro Infection Modelsmentioning
confidence: 99%
“…Phages have been shown to be stable in these models and the route of phage administration depends on the pathogen under investigation [ 44 , 59 , 67 ]. Through colonisation, survival and immune response studies, these models have been instrumental in determining phage therapeutic potential [ 44 , 59 , 67 ]. In a recent phage application study, carbapenem-resistant Acinetobacter baumannii infected Galleria mellonella larvae were treated with phage Bφ-R2096 via the proleg [ 68 • ].…”
Section: Efficacy Testing In Complex In Vitro Infection Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five of the published papers in this Special Issue refer to some strategies to prevent the development of phage-resistant mutants, namely by the use of combined approaches, such as the use of antibiotics [12,20], fatty acids [18], essential oil [19], and mucin [21] during phage treatment. Four of the papers include in vivo studies in animals [14,15,22] and plants [23].…”
mentioning
confidence: 99%